Expressing emotions in words: Facebook text-based comments in Tamil - Sinayah, Malarvizhi; Muthusamy, Paramasivam; Narayanan, Kannan; Abd Rahim, Normaliza (Universiti Putra Malaysia Press, 2015)
Language being used as a communication tool is embedded with emotions. Emotions in language are obvious in face-to-face (F2F) communication than in any other forms of communications. Media Richness Theory explains that the richer the media is the more successful communication will be and vice versa (Moczynski, 2010). This means text-based communication such as letters, e-mails, memo and so forth lacking of non-verbal cues like intonations, facial expressions, body movements and others, will not be as successful as F2F communication. On the other hand, there are also studies which have proven that computer mediated communication can convey non-verbal cues as effective as in F2F communication by manipulating the fonts with capitalization or using coloured fonts to express emotions (Mali, 2007; Boonthanom, 2004). Nevertheless, how is it possible to communicate non-verbal informations in a language like Tamil which does not have capital letters or colour code? The aim of this study is to identify the techniques used by Tamils in conveying emotions through words in facebook. This paper further discusses the frequent and helpful techniques used in Tamil communication. Samples chosen for this study were forty active facebook users who have good language competency in Tamil.